HIV evolution in response to HLA-restricted CTL selection pressures: a population-based perspective - Carlson, Jonathan M.; Brumme, Zabrina L. (Microbes and Infection, 2008)
Cytotoxic T-lymphocytes (CTL) recognize antigenic peptides displayed by HLA class I molecules on the infected cell surface and represent a major selective force driving HIV evolution through a phenomenon known as “immune escape”. Here we summarize recent advances in our understanding of the consequences of CTL escape on HIV evolution at the population level and discuss its implications for HIV vaccine design.